(untitled) (Aldershot, England, 2004)
The book offers guidelines on how to safely store materials that include paper, digital information, and sound recordings. Digital preservation and management are described in three separate chapters that has contributed an introduction outlining preservation principles and policies. The book also describes future trends and offers a lengthy chapter on the sources of information for digital preservation management
Keywords: Library materials,Archival materials,Tài liệu thư viện,Tài liệu lưu trữ; Conservation and restoration,Conservation and restoration,Bảo tồn và bảo quản,Bảo tồn và bảo quản